Improvements After Arthroscopic Treatment for Femoroacetabular Impingement Syndrome in High-Level Ice Hockey Players: 2-Year Outcomes by Player Position. Issue 3 (9th March 2021) - Lindman, Ida; Abrahamsson, Josefin; Öhlin, Axel; Wörner, Tobias; Eek, Frida; Ayeni, Olufemi R.; Senorski, Eric Hamrin; Sansone, Mikael
Background: Ice hockey players often undergo arthroscopic treatment for femoroacetabular impingement syndrome (FAIS); however, only a few studies have reported postoperative patient-reported outcomes. It has been debated whether player position is related to FAIS. Purpose: To evaluate the change in patient-reported outcome measures (PROMs) in high-level ice hockey players from presurgery to 2 years after arthroscopic treatment for FAIS. The secondary aim was to evaluate differences in outcomes among player positions and whether stick handedness is related to the side of the symptomatic hip. Study Design: Case series; Level of evidence, 4. Methods: Ice hockey players undergoing treatment for FAIS between 2011 and 2019 were prospectively included. Preoperative and 2-year follow-up scores were collected for the following PROMs: HAGOS (Copenhagen Hip and Groin Outcome Score), iHOT-12 (12-item International Hip Outcome Tool), EQ-5D (EuroQol–5 Dimensions) and EQ-VAS (EuroQol–Visual Analog Scale), Hip Sports Activity Scale, and visual analog scale for overall hip function. Player position and stick handedness were collected from public sources. Preoperative and follow-up outcomes were compared for the entire cohort and among player positions. Results: The cohort included 172 ice hockey players with a mean age of 28 years, a mean body mass index of 25.6, and a mean symptom duration of 46.3 months. In the 120 players with 2-year follow-up data, there was significant improvement in all PROMs as compared with presurgery: HAGOS subscales (symptoms, 47.5 vs 68.0; pain, 57.0 vs 75.8; activities of daily living, 62.5 vs 81.0; sports, 40.0 vs 64.7; physical activity, 30.9 vs 57.2; quality of life, 32.5 vs 57.8), iHOT-12 (45.2 vs 66.7), EQ-5D (0.59 vs 0.75), EQ-VAS (68.3 vs 73.2), and visual analog scale for overall hip function (49.6 vs 69.2) ( P < .0001 for all). At 2-year follow-up, 83% reported satisfaction with the procedure. There was no difference in the improvement in PROMs among player positions. Further, there was no significant relationship between stick handedness and side of symptomatic hip; however, because of the number of bilateral procedures and large number of left-handed shooters, no conclusions could be drawn. Conclusion: High-level ice hockey players undergoing arthroscopic treatment for FAIS reported improvements in PROMs 2 years after surgery, regardless of player position.